1994
DOI: 10.2503/jjshs.63.419
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Embryogenesis in Cymbidium through In Vitro Culture of Inner Tissue of Protocorm-Like Bodies

Abstract: SummaryEmbryogenic callus (EC) was initiated from inner tissue (IT) of protocorm-like bodies (PLB) of Cymbidium orchid cultured on Murashige and Skoog (MS) media supplemented with 1-naphthaleneacetic acid (NAA) or 2,4-dichlorophenoxyacetic acid (2,4-D). EC was obtained within 15 days on a MS medium containing 2 mg• liter -1 NAA or 0.5 mg • liter -1 2,4-D which was the most effective among the concentrations tested. When EC were transferred to a hormone-free MS medium, they produced protocorms within one month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 15 publications
2
23
0
2
Order By: Relevance
“…In most orchids, the process of somatic embryogenesis is part of the early steps of PLB formation (Begum et al, 1994). This is also true for explants of Oncidium Sharry Baby 'OM8'.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In most orchids, the process of somatic embryogenesis is part of the early steps of PLB formation (Begum et al, 1994). This is also true for explants of Oncidium Sharry Baby 'OM8'.…”
Section: Discussionmentioning
confidence: 98%
“…Instead, protocorm-like bodies (PLBs) are usually used as the target material for producing transgenic plants because of their easy maintenance and plant regeneration. Embryogenesis in Orchidaceae can be initiated from single or multiple cells (Begum et al, 1994;Chang and Chang, 1998;Ishii et al, 1998;Chen et al, 1999). Somatic embryos are usually from multiple cells, which results in a chimeric pattern in transformants (Park and Facchini, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Since then protocols for the tissue culture of Cymbidium by using flower stalks (Wang, 1988), pseudobulbs (Shimasaki and Uemoto, 1990), flower buds (Shimasaki and Uemoto, 1991), shoot tips (Morel, 1960(Morel, , 1964Wimber, 1963;Sagawa et al, 1966;Ueda and Torikata, 1968;Kim and Kako, 1984) and PLBs (Begum et al, 1994b;Tanaka, 2004a, 2004b;Huan et al, 2004) have been described. Studies on callus induction are scarcer, attributed to their slow growth and necrotic tendency (Begum et al, 1994a). Although callus was shown to be inducible from pseudobulb sections, rhizomes and roots of seedlings of Cymbidium ensifolium, a terrestrial orchid species, growth was slow, difficult, timeconsuming (12-18 months) and required high levels of PGRs.…”
Section: Introductionmentioning
confidence: 98%
“…Begum, Tamaki, Tahara, & Kako (1994) reported that callus formation from orchids used explants that contained meristematic cells or epidermal cells, suggesting that callus cells arise from these types of cells. Figure 3B shows the cross-section through the leaf tip explants which showed densely lower epidermis and mesophyll cells underwent dedifferentiation.…”
Section: Histology and Scanning Electron Microscope Observations On Ementioning
confidence: 99%